The classical photoactivated drug 8-methoxypsoralen and related compounds are effective without UV light irradiation against glioma cells. (October 2016) - de Oliveira, Diêgo Madureira; Ferreira Lima, Rute Maria; Clarencio, Jorge; Velozo, Eudes da Silva; de Amorim, Ilza Alves; Andrade da Mota, Tales Henrique; Costa, Silvia Lima; Silva, Fábio Pittella; El-Bachá, Ramon dos Santos
Abstract: Currently, there is no effective therapy for high grade gliomas. 8-Methoxypsoralen (8-MOP) is a compound used in the treatment of skin diseases combined with UV light irradiation. In this work, rat glioma C6 cells, normal astrocytes and human glioblastoma GL-15 cells comprised an in vitro model to evaluate the antitumor activity of 8-MOP. We found that 8-MOP promoted a time- and concentration-dependent reduction of cell viability in tumor, but not in normal cells. This effect was more evident in log-phase growing culture, indicating antiproliferative activity, which was confirmed by colony formation assay. Long-term effect of 8-MOP at low concentration was also attested. The concentrations used in the tests (0.02–0.4 mM) were lower than plasmatic concentration found in patients. Despite the treatment leads to considerable morphological changes and apoptosis when used at high concentrations, 8-MOP did not promote cell cycle arrest, change in migration pattern neither necrosis. In addition, we evaluated the effect of 8-MOP in MDA-MB-231, CT-26 and SCC-3 cell lines, derived from other kind of primary tumors, and found that CT-26 cells did not respond to 8-MOP treatment, indicating that this compound does not act through a generic mechanism. Coumarin derivatives structurally related to 8-MOP were screened for its antitumor potential and presented different patterns of biological activity, and then it was possible to suggest the relevance of 8-MOP molecular structure for antiproliferative action. Therefore, 8-MOP, a drug with an outstanding record of safety, and related coumarins are good prototypes for development of a new class of anti-glioma drugs. Graphical abstract: Highlights: The classical PUVA-therapy drug 8-MOP shows UV independent anti-glioma activity. 8-MOP slowed proliferation of resistant glioma cells, but not normal astrocytes. Anti-proliferative effect was also observed against cells from other kinds of tumor. Structure-activity relationship analysis was performed with related molecules. The results may indicate a new important use of a safe and well known drug.